Pemetaan Topografi Saluran Drainase Ruas Jalan Pangeran Diponegoro – Yos Sudarso Kota Samarinda Provinsi Kalimantan Timur - Muhammad Erik Riswan; Feri Fadlin; Radik Khairil Insanu; Muh. Akshar (Geomatics Technology Study Program, Politeknik Pertanian Negeri Samarinda, 2025)
This research is motivated by the frequent occurrence of waterlogging or flooding at the research location due to insufficient drainage capacity to accommodate the large volume of water. Therefore, topographic mapping of the drainage channels is conducted, with the data intended for planning the installation of pumps and normalization of the drainage channels. This study aims to describe the situational topography and present longitudinal and cross-sectional profile maps, as well as drainage volume information using AutoCAD Civil 3D 2022 and ArcMap 10.8. The topographic mapping of the drainage channels resulted in topographic maps, longitudinal profile (Long Section) maps, and cross-sectional profile (Cross Section) maps with a total of 202 coordinate points, an overall road length of 664 meters, 28 stations, divided into 25 meters for each station section, and a total drainage volume of 2104.17 cubic meters along Pangeran Diponegoro – Yos Sudarso road. Additionally, the presentation of the drainage channel slope was included. This research was conducted on Jalan Pangeran Diponegoro – Yos Sudarso in Samarinda City. The measurements in this study utilized the ComNav T300 Geodetic GPS using the Real-Time Kinematic (RTK) method.